VAPYRIN attenuates defence by repressing PR gene induction and localized lignin accumulation during arbuscular mycorrhizal symbiosis of Petunia hybrida. Issue 6 (25th December 2020) - Chen, Min; Bruisson, Sébastien; Bapaume, Laure; Darbon, Geoffrey; Glauser, Gaëtan; Schorderet, Martine; Reinhardt, Didier
Summary: The intimate association of host and fungus in arbuscular mycorrhizal (AM) symbiosis can potentially trigger induction of host defence mechanisms against the fungus, implying that successful symbiosis requires suppression of defence. We addressed this phenomenon by using AM‐defective vapyrin ( vpy ) mutants in Petunia hybrida, including a new allele ( vpy‐3 ) with a transposon insertion close to the ATG start codon. We explore whether abortion of fungal infection in vpy mutants is associated with the induction of defence markers, such as cell wall alterations, accumulation of reactive oxygen species (ROS), defence hormones and induction of pathogenesis‐related (PR) genes. We show that vpy mutants exhibit a strong resistance against intracellular colonization, which is associated with the generation of cell wall appositions (papillae) with lignin impregnation at fungal entry sites, while no accumulation of defence hormones, ROS or callose was observed. Systematic analysis of PR gene expression revealed that several PR genes are induced in mycorrhizal roots of the wild‐type, and even more in vpy plants. Some PR genes are induced exclusively in vpy mutants. Our results suggest that VPY is involved in avoiding or suppressing the induction of a cellular defence syndrome that involves localized lignin deposition and PR gene induction.